2022
DOI: 10.11604/pamj.2022.43.2.33592
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life among patient with chronic diseases during COVID-19 pandemic: a cross-sectional study

Abstract: Introduction in the last two years, COVID-19 has largely changed the rhythm of human life and overwhelmed the healthcare systems globally. Patients with pre-existing chronic diseases have worse outcomes during the COVID-19 pandemic. Methods an institution-based cross-sectional study was conducted from April 1-30, 2021. Data were collected using an interviewer-administered questionnaire and data extraction checklist. A systematic random sampling technique was used to sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In the background variables of our study, we found that participants with more chronic diseases had a lower quality of life, similar to many studies [12,[43][44][45][46]. These studies suggest that patients with chronic diseases have a lower quality of life due to the limitations imposed by their chronic conditions on physical functions.…”
Section: Discussionsupporting
confidence: 90%
“…In the background variables of our study, we found that participants with more chronic diseases had a lower quality of life, similar to many studies [12,[43][44][45][46]. These studies suggest that patients with chronic diseases have a lower quality of life due to the limitations imposed by their chronic conditions on physical functions.…”
Section: Discussionsupporting
confidence: 90%
“…People with chronic diseases often require regular medical attention and monitoring to manage their conditions effectively. When they experience illness or an exacerbation of their chronic condition, promptly seeking medical care becomes a priority [73]. Chronic diseases can make individuals more vulnerable to infections or complications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, elderly patients, who represent a substantial subset of the chronic disease population, may have faced amplified fears and problems in maintaining their routine care. Indeed, recent surveys showed that health-related quality of life of many patients with chronic disease and their caregivers was substantially deteriorated during the pandemic 14 50 53…”
Section: Discussionmentioning
confidence: 99%